Structural Definition of a Neutralization-Sensitive Epitope on the MERS-CoV S1-NTD - Wang, Nianshuang; Rosen, Osnat; Wang, Lingshu; Turner, Hannah L.; Stevens, Laura J.; Corbett, Kizzmekia S.; Bowman, Charles A.; Pallesen, Jesper; Shi, Wei; Zhang, Yi; Leung, Kwanyee; Kirchdoerfer, Robert N.; et al. (Cell reports (Cambridge), 2019)
Middle East respiratory syndrome coronavirus (MERS-CoV) emerged into the human population in 2012 and has caused substantial morbidity and mortality. Potently neutralizing antibodies targeting the receptor-binding domain (RBD) on MERS-CoV spike (S) protein have been characterized, but much less is known about antibodies targeting non-RBD epitopes. Here, we report the structural and functional characterization of G2, a neutralizing antibody targeting the MERS-CoV S1 N-terminal domain (S1-NTD). Structures of G2 alone and in complex with the MERS-CoV S1-NTD define a site of vulnerability comprising two loops, each of which contain a residue mutated in G2-escape variants. Cell-surface binding studies and in vitro competition experiments demonstrate that G2 strongly disrupts the attachment of MERS-CoV S to its receptor, dipeptidyl peptidase-4 (DPP4), with the inhibition requiring the native trimeric S conformation. These results advance our understanding of antibody-mediated neutralization of coronaviruses and should facilitate the development of immunotherapeutics and vaccines against MERS-CoV. [Display omitted] •The epitope for the neutralizing antibody G2 is confined to the apex of the MERS-CoV S1-NTD•G2 epitope is relatively well conserved•G2 IgG and Fab both neutralize pseudotyped and authentic MERS-CoV•G2 neutralizes by preventing the binding of DPP4 to trimeric S protein Wang et al. report the structural and functional characterization of the Middle East respiratory syndrome coronavirus (MERS-CoV)-neutralizing antibody G2. G2 recognizes a conserved epitope on the MERS-CoV S1 N-terminal domain (S1-NTD) and neutralizes MERS-CoV by interfering with binding to host receptor dipeptidyl peptidase-4 (DPP4). The findings are relevant for understanding the viral attachment mechanism and for the development of S1-NTD-based vaccines.